2017
DOI: 10.1097/hnp.0000000000000227
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Health Approaches Used in the Intensive Care Unit

Abstract: Intensive care units are care centers where, in order to provide the maximum benefit to individuals whose life is in danger, many lifesaving technological tools and devices are present, and morbidity and mortality rates are high. In the intensive care unit, when classic treatments fail or become unbearable because of side effects, complementary methods have been suggested to be the best alternative. Complementary health approaches are methods that are used both for the continuation and the improvement of the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Studies investigating the effects of reflexology on vital signs report that it generally decreases blood pressure and respiration rate, but the effect on pulse rate was reported to increase in some studies and decrease in others. [26][27][28][31][32][33] Mean scores of blood pressure, pulse rate, and respiration rate, which were within normal ranges in all groups, indicated no differences in vital signs between the groups after surgery at all measurement times. The present study found that reflexology caused minimal changes to vital signs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies investigating the effects of reflexology on vital signs report that it generally decreases blood pressure and respiration rate, but the effect on pulse rate was reported to increase in some studies and decrease in others. [26][27][28][31][32][33] Mean scores of blood pressure, pulse rate, and respiration rate, which were within normal ranges in all groups, indicated no differences in vital signs between the groups after surgery at all measurement times. The present study found that reflexology caused minimal changes to vital signs.…”
Section: Discussionmentioning
confidence: 99%
“…16,18,21,22,24,26,27 Recent studies about reflexology define it as an important supportive method that decreases pain and anxiety; brings relaxation and comfort; improves homeostasis, quality of life, blood flow, and regional function; increases immunity and sleep quality; decreases the level of cortisol; and increases endorphins, which is a body's natural pain-relieving chemical. 16,18,21,22,24,26,27 Although reflexology is a cost-effective method without adverse effects, it is not a well-known method in Turkey for relieving pain and anxiety. However, the use of reflexology in the postoperative period is a noninvasive nursing intervention that can contribute to quality of care and increase patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of integrative therapies in ICUs was investigated in eight quantitative studies (Feeney et al, 2017;Hayes & Cox, 1999;Madineh et al, 2017;Matsumoto-Miyazaki et al, 2018;Nicola et al, 2019;Ozlu & Bilican, 2017;Papathanassoglou et al, 2018;Salamati et al, 2017;) and five reviews (Erdogan & Atik, 2017;Jagan et al, 2019;Lee & Higgins, 2010;Richards et al, 2003;Tracy & Chlan, 2011; Table 1). Three case studies (Kreindler et al, 2014;Provancha-Romeo et al, 2019;Yalindag-Ozturk et al, 2011; Table 3) and one conference paper abstract (Hathaway et al, 2014;…”
Section: Theme 2: Interventions Using Integrative Therapiesmentioning
confidence: 99%
“…Integrative therapies seem to improve the adverse experiences of critical illness amongst patients (Snyder & Niska, 2003). Benefits include improved sleep; reduced heart rate, respiratory rate and blood pressure; reduced anxiety and discomfort; and lower uptake of analgesics and sedatives (Brenner & Krenzer, 2003;Erdogan & Atik, 2017;Estores & Frye, 2015;Kramlich, 2014Kramlich, , 2016Tracy & Chlan, 2011). Other benefits include fewer mechanical ventilation days, improved weaning from mechanical ventilation, patient satisfaction with care and reduced hospital costs (Papathanassoglou & Park, 2016).…”
Section: Benefits and Risksmentioning
confidence: 99%